Nanosized lead lanthanum titanate (PLT) ceramic powders synthesized by the oxidant peroxo method - Camargo, Emerson R.; Barrado, Cristiano M.; Ribeiro, Caue; Longo, Elson [UNESP]; Leite, Edson R. (Elsevier B.V. Sa, 2009)
For the first time it is reported the synthesis of lead titanate modified with rare earth by the oxidant-peroxo method (OPM). Lanthanum was added up to 20% in mol through the dissolution of lanthanum, oxide in nitric acid, followed by the addition of a solution of lead and lanthanum nitrate into an aqueous solution of titanium peroxo complexes. The amorphous precipitate formed was heat-treated at different temperatures in the range from 400 to 900 degrees C for crystallization. Powders were characterized by Raman spectroscopy and X-ray diffraction. Tetragonal perovskite structure was observed for the samples up to 15% of lanthanum substitution and cubic perovskite for sample with 20% of lanthanum. Crystallographic domains calculated by Scherrer equation showing a probable suppression of the crystallite growth in function of lanthanum content. It was observed shifting to lower frequencies of Raman modes in the range between 100 and 400 cm(-1) and the vanishing of the A1(2TO) and E(1LO) modes could be attributed to transition phase from tetragonal to cubic. Electronic microscopy image revealed that the powders annealed at height temperature are spherical with sharp size distribution. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Oxide materials; Chemical synthesis; X-ray diffraction; Crystal structure; Inelastic light scattering